1986
DOI: 10.1016/0035-9203(86)90185-9
|View full text |Cite
|
Sign up to set email alerts
|

A review of the malaria situation in Zimbabwe with special reference to the period 1972–1981

Abstract: Information on the prevalence, incidence, and geographical distribution of malaria in Zimbabwe is reviewed. Malaria control operations carried out during the last 30 years are briefly described together with available information of their impact on malaria. From 1972 to 1981, 51,962 positive blood slides were submitted to Blair Research Laboratory from health institutions, of which 97.8% were Plasmodium falciparum, 1.8% P. malariae and 0.3% P. ovale. Blood slide surveys undertaken from 1969 to 1981 during whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 3 publications
2
75
1
Order By: Relevance
“…We describe an analysis of the genetic variation of parasites in three areas of Zimbabwe using glurp, msp-1, msp-2 and neutral polymorphic microsatellite markers. These areas, Bindura, Chiredzi and Kariba, were described in a single study two decades ago to be of hypo-, meso-and hyperendemic transmission, respectively (Taylor and Mutambu, 1986). Transmission is seasonal in all these areas and the main mosquito vector is Anopheles arabiensis.…”
mentioning
confidence: 99%
“…We describe an analysis of the genetic variation of parasites in three areas of Zimbabwe using glurp, msp-1, msp-2 and neutral polymorphic microsatellite markers. These areas, Bindura, Chiredzi and Kariba, were described in a single study two decades ago to be of hypo-, meso-and hyperendemic transmission, respectively (Taylor and Mutambu, 1986). Transmission is seasonal in all these areas and the main mosquito vector is Anopheles arabiensis.…”
mentioning
confidence: 99%
“…In addition, elevation limited malaria transmission during the rainy season. Previous research in Zimbabwe suggested that malaria transmission does not typically occur at elevations exceeding 1,200 m. 1 Although the range of elevations for enumerated households was between 607 and 1,514 m, for sampled households, the range was limited to between 639 and 1,234 m. The limited range of elevation in the sampled households may be a result of logistical challenges reaching areas at higher elevations. Consequently, differences in malaria risk during the dry season related to elevation may have been masked by the underrepresentation of households at higher elevations.…”
Section: Discussionmentioning
confidence: 87%
“…Environmental factors previously identified as driving malaria transmission in the country include season, elevation, rainfall, temperature, and vapor pressure. 1,15,17,27 The model predicted higher risk of malaria among households sampled in the rainy season, located near the Mozambique border and further from health facilities. In addition, elevation limited malaria transmission during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Burma Valley in Eastern Zimbabwe and Kariba are malaria endemic areas. [24][25][26] Written informed consent was sought from all the participants together with assent from their parents/guardians to partake in the study. Each study participants' demographic data was collected and recorded during the two year follow up period.…”
Section: Study Design and Populationmentioning
confidence: 99%